Playing as a central activity in early childhood education - Sarmento, Teresa; Duarte Souto-Maior, Sara; Mendanha, Elsa (Aprender, 2024)
Playing as a natural activity for children is undeniable, proving direct and naturalistic observations in any social, cultural, or geographic context. This is a prerogative specific to human beings, during their childhood experience. If we look at an outdoor park, a refugee camp, a kindergarten classroom at non-prescribed times of activity, or any other space in which children have freedom of choice, play is manifest; it constitutes the most natural way for children to interact with others and situations.Playing has been, over time, much questioned by those who argue that childhood is a period of preparation for active life, contrary to the affirmation of playing as a child's right.Written by several hands, the reflection was challenged by the analysis of educational practices shared on a social network, from which the purposes of playing in everyday life are problematized. In this paper we are interested in discussing the relevance of playing in kindergarten, reflecting on how this is combined with the identity of these educational contexts, guided by educational purposes defined by legislative and curricular references, or by the social representations that exist given the frequency of these spaces.
Keywords: playing; educational purposes; pedagogical action